Impact of artificial intelligence on marketing - Mahabub Shaik (PT FORMOSA CENDEKIA GLOBAL, 2023)
The evolution of artificial intelligence (AI) has drastically changed the dynamics of today’s business world. One of the most significant applications of AI is in the field of marketing, which assists in enhancing performance. The current research aims at finding out the impact of AI in marketing. A thorough literature research was highlighted, providing a strong knowledge of AI and its use in marketing. Second, the researcher employed a qualitative study strategy that included semi-structured interviews with marketing professionals from several Indian companies. The researcher chose a sample size of fifteen marketing experts to interview. The study's findings emphasise the elements that influence AI integration in marketing, the benefits and obstacles of AI integration in marketing, as well as your company's pre and post AI marketing strategy, ethical considerations, and use of AI in the marketing industry. The study proposes integrating AI into marketing tasks in order to improve corporate performance and, as a result, achieve profitability and competitive advantage. This study also contributes to strategic marketing research by identifying research gaps that bridge strategic AI marketing practise and research in a systematic and rigorous manner.